Hepatitis B immunisation and immune status of nurses in a regional hospital in central South Africa - Emily M. Makola; Willem H. Kruger; Perpetual Chikobvu (South African Family Practice)
Background: The hepatitis B virus (HBV) is one of the most important biological occupational hazards for healthcare workers. A high percentage of HBV infections are attributable to percutaneous occupational exposure. This study aimed to describe the HBV immunisation and current immune status of all the nurses employed in a regional hospital in central South Africa.